Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations

Structural characterisation, anticancer properties, and BSA binding of 2,6-dipyrazinylpyridines: Insights from experiment and theory - Enumula, Sreenivasulu; Shaikh, Javed; Shaikh, Amin; Sheikh, Kounsar N.; Tambe, Pranav; Lande, Dipali N.; Gejji, Shridhar P.; Shaligram, Parth; Gonnade, Rajesh; Bhadbhade, Mohan; Ahmed, Khursheed (Journal of Molecular Structure, 2026)
The phenyl-(2,6-di-2-pyrazinyl)pyridine derivatives (L1, L2) were synthesized using a one-pot Krohnke-type method, starting from 2-acetylpyrazine and substituted benzaldehydes. Their structures were characterized using a combination of spectroscopic (NMR, HRMS) and single-crystal X-ray diffraction techniques, complemented by density functional theory (DFT). Single-crystal X-ray diffraction reveals that L1 crystallizes in the C2/c space group (T = 296 K) with its supramolecular assembly being stabilized by C-H & ctdot;N and pi-pi stacking interactions, whereas L2 facilitates C-H & ctdot;N, N-H & ctdot;pi bifurcated, and pi-pi* interactions. The bio-interaction properties of L1 were studied using fluorescence spectroscopy with bovine serum albumin (BSA) as a model protein. Fluorescence studies demonstrated L1 induces static quenching of BSA, with a binding constant of 5.15 x 104 mol & sdot;dm-3. Synchronous and three-dimensional fluorescence spectra further demonstrated that L1 brings forth significant conformational changes in BSA. The compounds were evaluated for cytotoxicity against the HCT-116 human colorectal cancer cell line.
Keywords: 2; 6-dipyrazinylpyridines; Bovine serum albumin interaction; Cytotoxicity (HCT-116 cells); Density functional theory; Halogenated derivatives; Single-crystal X-ray diffraction